Analyzing WhatsApp-Based Learning Interactions: Teaching Skills and Student Responses in Indonesian Higher Education - Widari, I.G.A.; Supriadi, Biat; Jazadi, Iwan (Jurnal Paedagogy, 2025)
This study explores how lecturers’ teaching skills and student responses manifest in WhatsApp-based learning environments in Indonesian higher education. Focusing on three classes of an “Introduction to Education” course, the research employs a qualitative descriptive approach and content analysis of chat transcripts and voice notes over 16 weeks. To frame the analysis, Asril’s model of basic teaching skills—covering questioning, explanation, reinforcement, and classroom management—was applied, alongside Hanifi and Rahayu’s taxonomy of student responses, which distinguishes between obedient, independent, pretentious, dependent, and stolid learner behaviors. Trustworthiness was ensured through inter-coder reliability checks and triangulation of text and voice-note data, enhancing the validity of findings. The study also draws on constructivist, connectivist, and rhizomatic pedagogy perspectives, with “rhizomatic” referring to decentralized, non-linear pathways of knowledge building. The results indicate that lecturers primarily used Opening and Closing, Further Questioning, and Reinforcement skills, while students most frequently responded as Independent learners, followed by Obedient and Pretentious types. These findings suggest that WhatsApp can support meaningful teaching–learning interaction, though its design limits collaborative and differentiated instruction. The study highlights the adaptability of core teaching competencies to digital platforms and emphasizes the need for strategic scaffolding to foster learner autonomy. Limitations include the scope of data and a lack of multimodal behavioral insight. The findings have implications for mobile pedagogy, digital curriculum planning, and future research in digitally mediated instruction.